Pengembangan Logistic Center Di Indonesia - Sitorus, Panal (Warta Penelitian Perhubungan, 2010)
Same problems of mrgo nwuement in Indonesin, among others not yet just in time sennces, not doorto door deliven;, the process of loading and unlonding at the port 5.5 clm;s, congestion, warehousingis Jar and spread mum; from the locntion of ports, industries and is still managed in conventional.Indonesw is in a position not competiti11e in tenns of Li:Jgistic Performance Index, which in 2007occupied the position 43 (score 3.01) from 150 countries. Research metlwds to obtain an opinion orperception of respondents with sampling techniques are purposively. Instntment of analysis is Importanceand Performance Analysis. Results of analysis showed that logistic cent.er meet the criteria.,connected 1mth the transportation SIJSfems, should the wide land area located near the harbor, connectedto the container terminals, high container slzip capacihj, minilnbilihJ of prinzan; commodities,advanced of infomzation and communication teclznologies.Keywords: wgistic cent.er development.